Cyberloafing, Work Environment, and Leadership on Performance and Job Satisfaction of Education Personnel at Sultan Syarif Kasim State Islamic University Riau - Prasetya, Andi Sugisty Eka; Nyoto; Putra, Rizaldi; Sultan, Fazal Mohamed Mohamed (Journal of Applied Business and Technology, 2023)
The purpose of this study was to determine the effect of Cyberloafing, Work Environment, and Leadership on the Performance and Job Satisfaction of Education Personnel at Sultan Syarif Kasim State Islamic University Riau. The method used in collecting data in this research is a questionnaire. The population in this study was 88 education staff or employees. The sample of this study used data analysis and PLS Structural Equation Modeling (SEM) analysis. The results show that Cyberloafing has no significant effect on Performance and Job Satisfaction, Work Environment Variables are not significant on Performance and Job Satisfaction, Leadership Variables are not significant on Performance but provide a significant positive on Job Satisfaction, and Performance Variables are not significant on Job Satisfaction.